Microbial Degradation of Naphthalene and Substituted Naphthalenes: Metabolic Diversity and Genomic Insight for Bioremediation - Mohapatra, Balaram; Phale, Prashant S. (Frontiers in Bioengineering and Biotechnology, 2021)
Low molecular weight polycyclic aromatic hydrocarbon (PAH) like naphthalene and substituted naphthalenes (methylnaphthalene, naphthoic acids, 1-naphthyl N-methylcarbamate, etc …) are used in various industries and exhibit genotoxic, mutagenic and/or carcinogenic effects on living organisms. These synthetic organic compounds (SOCs) or xenobiotics are considered as priority pollutants that pose a critical environmental and public health concern, worldwide. The extent of anthropogenic activities like emissions from coal gasification, petroleum refining, motor vehicle exhaust and agricultural applications decide the concentration, fate and transport of these ubiquitous and recalcitrant compounds. Besides physico-chemical methods to clean-up/removal, a green and eco-friendly technology like bioremediation, where in microbes with an ability to degrade SOCs completely or to non-toxic by-products, has been a safe, cost-effective and promising alternative. Various bacterial species from soil flora belonging to Proteobacteria (Pseudomonas, Pseudoxanthomonas, Comamonas, Burkholderia, Novisphingobium), Firmicutes (Bacillus, Paenibacillus) and Actinobacteria (Rhodococcus, Arthrobacter) displayed ability to degrade various SOCs. The metabolic studies, genomic and meta-genomics analyses have aided understanding the catabolic complexity and diversity present in these simple life forms which can be further applied for efficient biodegradation. Prolonged persistence of PAHs has led to the evolution of new degradative phenotypes through horizontal gene transfer using genetic elements like plasmids, transposons, phages, genomic islands and integrative conjugative elements. Systems biology and genetic engineering of either specific isolates or mock community (consortia) might achieve complete, rapid and efficient bioremediation of these PAHs through synergistic actions. In this review we highlight various metabolic routes and diversity, genetic make-up and diversity as well as cellular responses/adaptations by naphthalene and substituted naphthalene degrading bacteria. This will provide insights into the ecological aspects of field application and strain optimization for efficient bioremediation